1997
DOI: 10.1002/(sici)1097-4636(19970905)36:3<418::aid-jbm17>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural features of the bone response to a plasma-sprayed hydroxyapatite coating in sheep

Abstract: The intentions of this study were to characterize the macroscopic, microscopic, and structural aspects of a plasma-sprayed implant and to thoroughly investigate bone tissue response after its implantation in sheep. Therefore, we used scanning electron microscopy, transmission electron microscopy (TEM), high-resolution TEM, X-ray diffraction, and energy-dispersive X-ray analyses. Assessment of the biomaterial prior to implantation showed a coating with irregular outlines and varying thickness, mainly consisting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…High‐resolution transmission electron microscopy assessments of the interface between a titanium implant surface and bone tissue have shown that newly formed bone crystals develop as near as 20 nm to the biomaterial, after implantation 13, 14. On the other hand, ultrastructural investigations of the interface between calcium phosphate and bone tissue demonstrated bone‐bonding properties of such implant surfaces 15–17. Indisputably, titanium and calcium phosphates are appropriate biomaterials leading to osseointegration of bone replacing materials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High‐resolution transmission electron microscopy assessments of the interface between a titanium implant surface and bone tissue have shown that newly formed bone crystals develop as near as 20 nm to the biomaterial, after implantation 13, 14. On the other hand, ultrastructural investigations of the interface between calcium phosphate and bone tissue demonstrated bone‐bonding properties of such implant surfaces 15–17. Indisputably, titanium and calcium phosphates are appropriate biomaterials leading to osseointegration of bone replacing materials.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 On the other hand, ultrastructural investigations of the interface between calcium phosphate and bone tissue demonstrated bone-bonding properties of such implant surfaces. [15][16][17] Indisputably, titanium and calcium phosphates are appropriate biomaterials leading to osseointegration of bone replacing materials.…”
Section: Discussionmentioning
confidence: 99%
“…However, to move toward an understanding of collagen-mineral interactions we need to move toward nanoscale and atomic characterizations, where TEM plays a key role. A plethora of observations that have laid foundations for understanding osseointegration of various biomaterials have been made using TEM in the 1990s. The premise of TEM imaging relies on electrons passing through an electron transparent specimen. Once the beam is transmitted, both inelastic and elastic scattering events can be detected, and be used for imaging and elemental analysis.…”
Section: At the Nano And Atomic Scalementioning
confidence: 99%
“…3,4 Calcium phosphates based materials have attracted considerable interest for orthopaedic and dental applications. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] These biomaterials belong to an important family of bioceramics resembling the part of calcified tissues, particularly hydroxyapatite (Hap), tricalcium phosphate (TCP) and fluorapatite (Fap).…”
Section: Introductionmentioning
confidence: 99%